Contribuição anatômica do lenho à taxonomia do antigo gênero Acacia Mill. (Fabaceae) - Machado, Paulo Fernando dos Santos (2016)
This study aimed to describe the wood anatomy of ten species of the former genus Acacia Mill., as well as to conduct a quantitative agglomerative analysis with 25 species of the same genus, in order to recognize wood anatomical features of diagnostic value to the genera segregated from Acacia Mill. in 2005. The following species were investigated and described, according to IAWA Committee: Acacia acuminata A. Gray, Acacia cambagei R.T. Baker, ex Baker, Acacia harpophylla F. Muell. ex Benth., Acacia koa A. Gray, Acacia rhodoxylon Maiden, Acacia richii A. Gray, Senegalia martiusiana (Steud.) Seigler e Ebinger, Vachellia collinsii Saff., Vachellia nilotica (L.) P. J. H. Hurter e Mabb., e Vachellia planifrons (Wight e Arn.) Ragup., Seigler, Ebinger e Maslin. To the Cluster analysis, anatomical data of another 15 species were collected from the literature. All species share the following features of large occurrence in Fabaceae: diffuse-porous wood; simple perforation plates; vestured intervessel pits; paratracheal parenchyma; libriform fibers; and homogeneous rays. The presence of septate fibers allows to distinguish all the studied species of Senegalia Raf. The occurrence of conspicuous large rays, conjugated with abundant axial parenchyma allows to set apart all Vachellia species from the seven ones, that belongs to the genus Acacia Mill.